Avaliação das propriedades do Aço inoxidável 304 de baixa espessura, após soldagem TIG - Ramos, Douglas Henrique (2024)
This work evaluates the mechanical and microstructural properties of low-thickness 304 stainless steel, subjected to the Tungsten Inert Gas (TIG) welding process. Using an ER308L electrode and autogenous welding, samples of 304 stainless steel were analyzed to understand the effects of these welding techniques on the characteristics of the material. The results indicate that TIG welding, with both methods, significantly impacts steel properties, such as corrosion resistance, mechanical strength and ductility. The microstructural analysis revealed changes in the grains and the formation of intermetallic phases, highlighting the importance of a detailed post-welding evaluation. It is concluded that TIG welding can substantially change the properties of thin 304 stainless steel, being crucial for the optimization of industrial processes.